Heterogeneity in macrophages along the cochlear spiral in mice: insights from SEM and functional analyses - Zhang, Celia; Ye, Mengxiao; Bush, Peter; Hu, Bo Hua (Frontiers in Cellular Neuroscience, 2023)
The susceptibility of sensory cells to pathological conditions differs between the apical and basal regions of the cochlea, and the cochlear immune system may contribute to this location-dependent variability. Our previous study found morphological differences in basilar membrane macrophages between the apical and basal regions of the cochlea. However, the details of this site-dependent difference and its underlying structural and biological basis are not fully understood. In this study, we utilized scanning electron microscopy to examine the ultrastructure of macrophages and their surrounding supporting structures. Additionally, we examined the phagocytic activities of macrophages and the expression of immune molecules in both apical and basal regions of the cochlea. We employed two mouse strains (C57BL/6J and B6.129P-Cx3cr1 tm1Litt /J) and evaluated three experimental conditions: young normal (1-4 months), aging (11-19 months), and noise-induced damage (120 dB SPL for 1 hour). Using scanning electron microscopy, we revealed location-specific differences in basilar membrane macrophage morphology and surface texture, architecture in mesothelial cell layers, and spatial correlation between macrophages and mesothelial cells in both young and older mice. Observations of macrophage phagocytic activities demonstrated that basal macrophages exhibited greater phagocytic activities in aging and noise-damaged ears. Furthermore, we identified differences in the expression of immune molecules between the apical and basal cochlear tissues of young mice. Finally, our study demonstrated that as the cochlea ages, macrophages in the apical and basal regions undergo a transformation in their morphologies, with apical macrophages acquiring certain basal macrophage features and vice versa. Overall, our findings demonstrate apical and basal differences in macrophage phenotypes and functionality, which are related to distinct immune and structural differences in the macrophage surrounding tissues.